Analisis Kemampuan Komunikasi Matematis Berdasarkan Self-Efficcy Siswa Dalam Pemecahan Masalah Matematika - Riski Supriyati; Supriyono; Nila Kurniasih (Jurnal Inovasi Pendidikan Matematika (JIPM), 2021)
This study aims to determine mathematical communication skills based on students' self-efficacy in solving mathematics problems in junior high schools. This research method is a qualitative descriptive research method. The subjects of this study were students of class VIIC on the material of the Association. The technique of taking this subject uses a purposive technique. Selection of subjects based on the results of filling in the student self-efficacy scale. Next, the subject selection was taken by two students who had high self-efficacy and two students with low self-efficacy. Data collection techniques used questionnaires, tests, and field notes. The research instrument used a questionnaire and test. Data analysis techniques use data reduction, data display, and conclusion drawing. The results of this study indicate that students with high self-efficacy are able to express their mathematical ideas in the form of mathematical communication to find solutions to problems well. They look firm and confident in communicating their mathematical ideas into mathematical symbols and models. Students with low self-efficacy still have difficulty communicating their mathematical ideas and are not thorough in solving problems. They are also often less precise in using mathematical terms and notations.